"It's a Tug of War Between the Person I Used To Be and the Person I Want To Be": The Terror, Complexity, and Limits of Leaving Crime Behind. (April 2019) - Buck, Gillian
This article draws upon an ethnographic study of peer mentoring in the United Kingdom criminal justice system. It examines how people attempting to desist from criminal lifestyles often experience a period of crisis, characterized by unsettling practical and personal losses. Through interviews with peer mentors and mentees, and observations of mentoring practices, this study renders this sense of adversity visible. It also reveals the ways in which peer mentors may alleviate the weight of the crisis, by providing a blueprint of change, while appearing to be nonauthoritarian. These are important components given that mentees often feel untethered from known ways of being and describe their interactions with authority figures as embattled. An interesting secondary effect which emerges here is that peer mentors appear to shift the perceptions of external observers. This is a vital feature, given that sustained desistance from crime requires contexts conducive to such changes.